ENHANCING PROSTHETIC LONGEVITY AND FRACTURE RESISTANCE BY COBALT-CHROMIUM FRAMEWORK INTEGRATION IN MANDIBULAR COMPLETE DENTURES — A CASE SERIES - Dr.Mithileshwari Patil; Dr. Abhijit Deshpande; Dr.Virsen Patil; Dr.Snehal Shende; Dr.Sampathkumar N.; Dr.Karthik S.M; Dr. Nikhil Tantak (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Polymethyl methacrylate (PMMA), widely used in prosthodontics, often fails under heavy masticatory forces due to low impact strength and fatigue resistance. Cobalt-chromium metal frameworks offer a durable alternative, particularly in complex cases. This case series highlights three examples: a patient with repeated PMMA denture fractures resolved with a cobalt-chromium design, a tongue-tie patient with opposing natural teeth stabilized by a metal framework, and an OSMF patient with limited oral access successfully rehabilitated using a metal-based denture. While metal frameworks may have aesthetic and weight limitations, their advantages in fracture resistance, longevity, and functionality make them invaluable for challenging clinical scenarios.